Mt1 transgenic mice: a new model for the study of skin and hair follicle regeneration after wounding - LEI LEI (The Graduate School, Ajou University, 2024)
Metallothionein 1 (MT1), a heavy metal-binding protein, is present in various organs including the skin. It is highly expressed in hair follicles and epidermis. In the present study, the regeneration process of hair follicles and skin was followed by generating Mt1 transgenic mice. Mt1-marked epidermal cells are used for stratification and maintenance of hair follicles, but not for cell proliferation, opening new possibilities for skin regeneration studies. After removal of the epidermis, dermis and hair follicles by punching the wound, it was found that Mt1-negative epidermal keratinocytes began to migrate toward the center of the wounds and divide violently, forming a stretched epidermis (SE) at the edge of the wounds. Meanwhile, the dermal regeneration process under the SE is relatively slow, and low-density fibers (LDFs) fill the wound bed. When the SE completely covers the entire wound area, a cleft in the epidermis can be observed. However, as the SE continues to desquamate, it gradually disappears and normalizes. The LDFs in the regenerated area of the dermis gradually decrease, and the existing hair follicles outside the wound move towards the regenerated area as the wound heals, forming a "regenerating hairless triangle zone" (RHTZ) where the hair follicles eventually rearrange themselves, but no new hair follicles are formed in this area. Therefore, Mt1-positive cells were found in all hair follicles in the regenerating area. These results suggest that Mt1 transgenic mice can be used as a research model for skin and hair regeneration, and that ‘hair regeneration’ may result from the rearranging number of hair follicles outside the injured area into the regenerated area.
학위논문(석사)--생명과학과,2024. 2
Keywords: epidermis; hair follicle; metallothionein; regeneration; wound healing